Transmission of iriban culture in water resources management in Lerep Village, West Ungaran, Semarang - Riskiyanto, Riskiyanto; Setyowati, Dewi Liesnoor; Atmaja, Hamdan Tri (JESS (Journal of Educational Social Studies), 2021)
Culture plays an important role in human activities to meet the needs of life from generation to generation. Adolescents play an important role as agents of cultural transmission because they will do it in the future. The iriban culture in one location in Dusun Lerep was lost for a while and has now been revived. This study aims to analyze the current implementation of iriban in Lerep Hamlet and the process of transmitting the iriban culture to the younger generation. This study uses qualitative methods, data is taken using interviews and analyzed using domain and taxonomy analysis. The results of this study indicate that the implementation of the Iriban undergoes changes and innovations in several aspects. Transmission of culture to adolescents through participation, parental guidance, and cultural exhibitions. The transmission is in the form of values, customs, and social habits. So the habitus in the iriban in Lerep Hamlet is related to the process of transmitting the iriban culture in the form of a process of transferring knowledge from parents to their children through the cultural realm.